Clinical outcome of adjuvant endocrine treatment according to Her-2/neu status in breast cancer - James, Rani (Medknow Publications, 2011)
BACKGROUND & OBJECTIVES: An association between over-expression of proto-oncogene Her-2/neu and resistance to tamoxifen in estrogen receptor (ER) positive, primary and metastatic breast cancer has been suggested. HR+/Her-2/neu+ patients have a poor response to endocrine therapy, making this group a matter of debate. The present study was carried out to examin whether Her-2/neu expression in breast cancer patients predicted tamoxifen effectiveness. METHODS: An enzyme-linked immunosorbent assay (ELISA) specific for the extracellular domain of the Her-2/neuoncoprotein product was used to detect serum Her-2/neu levels in 207 patients with histological confirmed breast cancer. Tissue Her-2/neu expression was studied in 100 breast cancer patients by immunohistochemistry (IHC) and compared with serum Her-2/neu levels by ELISA. RESULTS: Among 207 histologically confirmed breast cancer patients, 53 were serum Her-2/neu positive. Patients who were treated with surgery, chemotherapy, and radiotherapy showed significantly (P<0.05) reduced serum Her-2/neu levels, showing good response to treatment. Patients who were treated with tamoxifen in addition to the above regimen did not show any significant reduction in serum Her-2/neu levels showing resistance to treatment. INTERPRETATION & CONCLUSIONS: The present findings study support the hypothesis that Her-2/neu overexpression contributes to tamoxifen resistance. Trastuzumab or other growth factor inhibitors should be used in combination with tamoxifen, since monotherapy is not likely to be optimal in HR+/Her-2/neu+ tumours.